KANDUNGAN FENOL PADA PINEKUHE YANG DIOLAH DENGAN ASAP CAIR DAN PENGASAPAN KONVENSIONAL - Jefri A. Mandeno; Mukhlis A. Kaim (Jurnal Ilmiah Tindalung, 2021)
Tujuan dari penelitian ini adalah untuk mengetahui kandungan fenol pada ikan asap pinekuhe dengan asap cair dan dengan pengasapan konvensional. Penelitian menggunakan Rancangan deskriptif kualitatif dengan memberikan gambaran proses dan hasil penelitian melalui gambar, tabel maupun histogram. Perlakuan dalam penelitian adalah sebagai berikut: (A) Ikan asap pinekuhe ang direndam dalam asap cair lalu dikeringkan, (B) Ikan asap pinekuhe yang dkeringkan, direndam dalam asap cair lalu dikeringkan, (C) Ikan asap pinekuhe direndam dalam asap cair lalu dikeringkan dan (D) Ikan asap pinekuhe dari pengasapan konvensional dengan bahan bakar biasa. Kesimpulan dari hasil penelitian ini bahwa ikan asap cair yang dikeringkan kemudian direndam dalam asap cair memiliki kadar fenol yang lebih tinggi jika dibandingkan dengan ikan asap yang diolah dengan metode pengasapan konvensional, yaitu dengan menggunakan bahan bakar cangkang pala. Kadar fenol tertinggi yaitu pada perlakuan B (15,77%) dan kadar fenol terendah yaitu pada perlakuan C (10,2%). The purpose of this study was to determine the phenol content of pinekuhe smoked fish with liquid smoke and conventional smoking. The study used a qualitative descriptive design by providing an overview of the research process and results through pictures, tables, and histograms. The treatments in the study were as follows: (A) Pinekuhe smoked fish soaked in liquid smoke then dried, (B) Pinekuhe smoked fish that was dried, soaked in liquid smoke then dried, (C) Pinekuhe smoked fish was immersed in liquid smoke then dried and (D) Pinekuhe smoked fish from conventional smoking on ordinary fuel. The conclusion from the results of this study is that smoked fish that is dried and then immersed in liquid smoke has a higher phenol content when compared to smoked fish processed by conventional smoking methods, namely using nutmeg shell fuel. The highest phenol content was in treatment B (15.77%) and the lowest phenol content was in treatment C (10.2%) Abstract: The purpose of this study was to determine the phenol content of pinekuhe smoked fish with liquid smoke and conventional smoking. . The study used a qualitative descriptive design by providing an overview of the research process and results through pictures, tables, and histograms. The treatments in the study were as follows: (A) Pinekuhe smoked fish soaked in liquid smoke then dried, (B) Pinekuhe smoked fish that was dried, soaked in liquid smoke then dried, (C) Pinekuhe smoked fish was immersed in liquid smoke then dried and (D) Pinekuhe smoked fish from conventional smoking on ordinary fuel. The conclusion from the results of this study is that smoked fish that is dried and then immersed in liquid smoke has a higher phenol content when compared to smoked fish processed by conventional smoking methods, namely using nutmeg shell fuel. The highest phenol content was in treatment B (15.77%) and the lowest phenol content was in treatment C (10.2%).